Leitura e Letramento Literário: Uma Experiência nos Anos Finais do Ensino Fundamental: Reading and literary lettering: an experience in the final years of fundamental education (Revista Cocar, 2022)
O presente artigo propõe em seu objeto de estudo ampliar o campo da significação da leitura e do letramento literário com estudantes dos anos finais do ensino fundamental de uma escola pública no estado da Bahia. O objetivo foi o de expandir as competências de leitura e escrita, bem como introduzir o letramento literário. A abordagem da pesquisa foi qualitativa e o delineamento seguiu a pesquisa aplicada em educação. Os procedimentos de ação no campo empírico centraram-se na realização de círculos de leitura. Os resultados refletem a ampliação do mundo leitor, a criticidade dos jovens sobre si e sua relação com a linguagem literária. Palavras-chave: Letramento literário; Leitura e escrita; Ensino fundamental. AbstractThis present article proposes in its object of study to expand the field of meaning of reading and literary literacy with students in the final years of elementary school in a public school in the state of Bahia. The objective was to expand reading and writing skills and introduce literary literacy. The research approach was qualitative and the design followed applied research in education. The action procedures in the empirical field focused on reading circles. The results reflect the expansion of the reading world, the young people's criticality of themselves and their relationship with literary language.Keywords: Literary literacy. Reading and writing. Elementary school. AbstractThis present article proposes in its object of study to expand the field of meaning of reading and literary literacy with students in the final years of elementary school in a public school in the state of Bahia. The objective was to expand reading and writing skills and introduce literary literacy. The research approach was qualitative and the design followed applied research in education. The action procedures in the empirical field focused on reading circles. The results reflect the expansion of the reading world, the young people's criticality of themselves and their relationship with literary language.Keywords: Literary literacy. Reading and writing. Elementary school.